Anecdote of the Ōmura laboratory and the discovery of avermectin†. Issue 1 (2nd January 2017) - Iwai, Yuzuru
Abstract : I first met Professor Ōmura, Distinguished Emeritus Professor, at The Kitasato Institute (Kitaken) when I was 28 years old. Since then, he has been my respectful supervisor as well as mentor. Looking back on those memories, I am deeply honored to write about the discovery and development of avermectin.